2020
DOI: 10.21203/rs.3.rs-16887/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of the molecular mechanism and diagnostic biomarkers in the thoracic ossification of the ligamentum flavum using metabolomics and transcriptomics

Abstract: Background: To establish a metabolite fingerprint of ossification of the thoracic ligamentum flavum (OTLF) patients using liquid chromatography-mass spectrometry (LC-MS) in combination with transcriptomic data and explore the potential molecular mechanism of pathogenesis. Results: The study cohort was composed of 25 patients with OTLF and 23 healthy volunteers as a control group. 37 metabolites were identified out by UPLC-MS including uric acid and hypoxanthine. 9 metabolites, including uric acid and hypoxanth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…To date, genetic, stress, ageing, in ammatory and metabolic factors have been found to be associated with the TOLF, whose etiological heterogeneity may indicate distinctive pathological phenotypes. [5][6][7][8][9] Except for susceptible middle-aged and elderly people, anecdotal observations indicated that a clinical subset of younger patients with obesity also suffered from severe or even diffuse TOLF. Additionally, concrete evidence has identi ed obesity as an independent causal factor for the development of TOLF in nonelderly adults.…”
Section: Introductionmentioning
confidence: 99%
“…To date, genetic, stress, ageing, in ammatory and metabolic factors have been found to be associated with the TOLF, whose etiological heterogeneity may indicate distinctive pathological phenotypes. [5][6][7][8][9] Except for susceptible middle-aged and elderly people, anecdotal observations indicated that a clinical subset of younger patients with obesity also suffered from severe or even diffuse TOLF. Additionally, concrete evidence has identi ed obesity as an independent causal factor for the development of TOLF in nonelderly adults.…”
Section: Introductionmentioning
confidence: 99%